Improvement of a MALDI-TOF database for the reliable identification of Candidozyma auris (formally Candida auris) and related species - Hui-Hui Zhu; Miao-Miao Liu; Teun Boekhout; Qi-Ming Wang (Microbiology Spectrum)
ABSTRACT Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is a promising technique for the rapid identification microorganisms. The aim of this study was to create a new database for the accurate identification of Candidozyma auris (formerly known as Candida auris) and 11 species of the Candidozyma haemuli species complex, including C. chanthaburiensis, C. duobushaemuli, C. haemuli, C. heveicola, C. khanbhai, C. konsanensis, C. metrosideri, C. ohialehuae, C. pseudohaemuli, C. ruelliae, and C. vulturna. Seventy-one Candidozyma isolates from different national institutions were studied. Thirty-seven strains were used to create a MALDI-TOF (microTyper MS) database using the formic acid extraction method. The validation of this database was performed with 34 other strains of the genus Candidozyma, and the result was compared with the identification results when using DBRs v1.0.0.4 (Tianrui, China). Our library allowed a 100% identification of the evaluated strains with all strains showing log scores of >2.0. Repeatability and reproducibility tests result showed a coefficient of variation of the log score values of less than 5%. The MALDI-TOF MS system can identify C. auris and related species quickly and accurately. This method will play a crucial role in accurately diagnosing infectious agents of the genus Candidozyma in clinical practice.IMPORTANCEImportance Candidozyma auris, also known as Candida auris, has quickly spread across the world, and prompt identification of C. auris from infected individuals is critical. However, a standard identification method is lacking for the identification of C. auris in clinical and public health laboratories. To make matters worse, its biochemical assimilation profile was found to be similar to that of closely related and even no-related species, leading to frequent misidentification. To improve diagnostics of this and closely related species, we created a database of reference mass spectra resulting in the efficient and correct identification of all Candidozyma species by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Moreover, potential pathogenic species of Candidozyma can be effectively identified by MALDI-TOF MS, and differentiated from non-clinically relevant phylogenetic relatives. Thus, MALDI-TOF MS may help expedite laboratory diagnosis and treatment of C. auris and related species of clinical importance and help the clinician to decide on early treatment.